E catou pella nave e nom viu rem, que a noite era muito escura Sobre o estatuto de rem em Português Antigo - Pinto, Clara (Revista da Associação Portuguesa de Linguística, 2019)
This article presents the grammaticalization path of the item rem as an indefinite minimizer (cf. Pinto 2015) in Old Portuguese. Originating from the common noun rem, the indefinite minimizer presents several features that indicate it was on its way to become a more functional item. It could be distinguished from the common noun rem due to its lack of referential meaning and other nominal properties such as the absence of ɸ-features and the occurrence as a bare noun. Nevertheless, it disappears very early from the language, not going beyond the status of a weak negative polarity item. One of the reasons that is believed to have favoured its disappearance was the competition with other identical items, namely the indefinite minimizer cousa ‘thing’ and the negative indefinite nada ‘nothing’. Contrary to what is verified for Portuguese rem, in other Romance languages such as Catalan or French, the descendants of the Latin res survived as polarity items (Catalan res, French rien), although with different degrees of grammaticalization.